Separation of bivalent anti-T cell immunotoxin from Pichia pastoris glycoproteins by borate anion exchange - Jung Hee Woo; David M. Neville (BioTechniques)
A major problem encountered in the large-scale purification of the bivalent anti-T cell immunotoxin, A-dmDT390-bisFv(G4S), from Pichia pastoris supernatants was the presence of host glycoproteins exhibiting similar charge, size, and hydrophobicity characteristics. We overcame this problem by employing borate anion exchange chromatography. The borate anion has an affinity for carbohydrates and imparts negative charges to these structures. We found that at a concentration of sodium borate between 50 and 100 mM, the nonglycosylated immunotoxin did not bind to Poros 50 HQ anion exchanger resin, but glycoproteins, including aggregates related to the immunotoxin, did. By using this property of the immunotoxin in the presence of sodium borate, we successfully developed a 3-step purification procedure: (i) Butyl-650M hydrophobic interaction chromatography, (ii) Poros 50 HQ anion exchange chromatography in the presence of borate, and (iii) HiTrapTM Q anion exchange chromatography. The final preparation exhibited a purity of greater than 98% and a yield of greater than 50% from the supernatant. Previously, boronic acid resins have been used to separate glycoproteins from proteins. However, combining borate anion with conventional anion exchange resins accomplishes the separation of the immunotoxin from glycoproteins and eliminates the need to evaluate nonstandard resins with respect to good manufacturing practice guidelines.